Modification of the FRET rate in quantum dot structures - Gounko, Iouri; Bradley, Louise (My University, 2011)
Förster resonant energy transfer (FRET) can be applied to create energy flow on the nano-scale for light harvesting, colour conversion or sensing applications. The performance of such devices depends on the efficiency of the energy transfer process between the donors and acceptors. In order to achieve high FRET efficiencies, the FRET rate has to dominate over the other donor decay rates. The FRET rate depends on the donor-acceptor separation, the acceptor concentration and it has also been proposed that it can be strongly enhanced by localized surface plasmons supported by metal nanoparticles. The impact of these different parameters on the FRET rate in a CdTe quantum dot donor-acceptor bilayer structure is presented. The quantum dot structures, prepared by a layer-by-layer deposition technique, were characterized by steady-state photoluminescence (PL) and absorption spectroscopy as well as time-resolved PL measurements. The FRET rate of the different structures was determined from the time-resolved donor PL decays and its separation and concentration dependence was compared with FRET theory.
Proceedings of the International Conference on Transparent Optical Networks 2011
International Conference on Transparent Optical Networks 2011
Keywords: Förster resonant energy transfer; Nanocrystal quantum dots; Localized surface plasmon resonances; Colloidal gold nanoparticles; Time-resolved emission decay